Growth Profile in Pediatric Patients with Diabetes Mellitus at Dr. M. Djamil General Hospital, Padang - Michael Mettafortuna Sephberlian; Eka Agustia Rini (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Diabetes mellitus (DM) is a glucose metabolism disorder characterized by chronic hyperglycemia that often occurs and is a major health problem. During puberty, increased Growth Hormone (GH) secretion results in increased insulin resistance. This study aimed to describe the growth profile of pediatric patients with diabetes mellitus at Dr. M. Djamil General Hospital. Methods: A descriptive retrospective study with conducted by collecting data on body height, HbA1C level, and status of puberty from medical records at the pediatric ward of Dr. M. Djamil General Hospital from January 2019 - December 2020. Results: The sample was 67 (63 T1DM, 2 T2DM, and 2 double DM). Ten of them with short stature (8 with poor metabolic control). Conclusion: Children with DM may experience growth disturbance.